Molecular Modelling Analyses of the Relative Stability of Alkenes, Arenes and Their Epoxides and Diols - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
Polyaromatic hydrocarbons often acquire carcinogenicity as a result of their activation due to the formation of epoxides and diols. Epoxides are formed when an oxygen atom binds across a carbon-to-carbon double bond. In this study, molecular modelling analyses using molecular mechanics, semi-empirical calculations were carried out to investigate the relative stability of aikenes, arenes, their epoxides and diols. The results of calculation show that the formation of epoxides and diols are spontaneous with the Gibb's free energy changes (ΔG) being negative for both. The calculated results also show that the stability of the epoxide formed depends on the position of double bond at which oxygen binds, giving credence to the idea of site-specificity in metabolic activation.